Pengembangan Aplikasi Android Rekomendasi Kelompok Tempat Pembelian Kerajinan Tangan Khas Malang dengan Metode Topsis-Borda - I Made Wira Satya Dharma; Ratih Kartika Dewi; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Malang is a city that has a big tourist attraction in the province of East Java. Many typical handicrafts that can be made as souvenirs for people who visit this city. Previously there was a recommendation system in the selection of typical handicrafts in Malang, but recommendations were only for 1 user. Usually the visitors, tourists, students and Malang society often choose the place of souvenirs or handicrafts by discussing together. Therefore, it will develop a recommendation application using the GDSS approach that can help visitors, tourists, students and Malang society get a recommendation for a place of handicrafts typical of Malang that is done in groups. Therefore, developing a recommendation application using the GDSS approach can help visitors, tourists, students and society Malang get recommendations for the typical handicrafts of Malang that are done in groups. In this study using the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method to sort the selection recommendations and Borda for the group voting method. This study was tested on 5 users and resulted in 74.5 of usability testing using the SUS questionnare and the results was in the acceptable category and included in the Good category.